Remittances and household expenditure patterns in India and selected states. (2nd January 2017) - Mahapatro, Sandhya; Bailey, Ajay; James, K.S.; Hutter, Inge
Abstract : Using the nationally representative data drawn from NSSO 64th round, this paper investigates the impact of remittances both internal and international on the expenditure patterns of households in India, with special focus on Uttar Pradesh and Kerala and Karnataka. To control for selectivity bias and to assess the average impact of remittances on household expenditure items, the present paper applies propensity score matching technique. The estimates reveal that compared to non-recipient households, households receiving remittances spend less on food and more on education and health care. Increasing expenditure with remittance flow on these critical variables signifies the positive impact of remittances on household development. The impact of international remittances on these indicators weighs more than internal. In line with the optimistic view, the findings of the present study show that remittances enhance household well-being.